Aspiration Risk Factors in Hospitalized Patients Following Trauma - Lamb, Augustus; Martinez, Maximillian; Halimeh, Bachar; Chen, Guoqing; Winfield, Robert (Kansas Journal of Medicine, 2022)
Introduction. Risk factors for aspiration are not well characterized in the trauma patient population.  Improved understanding is important due to features of this patient population that place them at high risk for morbidity and mortality with aspiration. Methods. In a retrospective analysis of a select group of patients who suffered a traumatic injury, candidate and significant associations were identified for aspiration events.Results. Of the 146 patients analyzed, 57 (39%) had at least one documented aspiration event while 89 (60.9%) patients had none.  Multivariate logistic regression found a significant association between impaired consciousness and aspiration events (p = 0.012).Conclusions. To our knowledge, this study is a novel characterization of trauma patients likely to have experienced an aspiration event while hospitalized.  Our results suggest candidate risk factors for aspiration exist in a trauma-specific population.  Impaired consciousness is likely to show a significant association with aspiration in trauma patients in future studies.